129Xe and 131Xe nuclear magnetic dipole moments from gas phase NMR spectra. (16th January 2015) - Makulski, Włodzimierz
Abstract : 3 He, 129 Xe and 131 Xe NMR measurements of resonance frequencies in the magnetic field B0 = 11.7586 T in different gas phase mixtures have been reported. Precise radiofrequency values were extrapolated to the zero gas pressure limit. These results combined with new quantum chemical values of helium and xenon nuclear magnetic shielding constants were used to determine new accurate nuclear magnetic moments of 129 Xe and 131 Xe in terms of that of the 3 He nucleus. They are as follows: μ( 129 Xe) = −0.7779607(158)μN and μ( 131 Xe) = +0.6918451(70)μN . By this means, the new 'helium method' for estimations of nuclear dipole moments was successfully tested. Gas phase NMR spectra demonstrate the weak intermolecular interactions observed on the 3 He and 129 Xe and 131 Xe shielding in the gaseous mixtures with Xe, CO2 and SF6 . Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The ratio of the NMR spin precession frequencies of 3 He and both magnetic active xenon nuclei 129 Xe and 131 Xe were measured. It was carried out by precise recording of NMR spectra for small amounts of xenon/3‐helium in gaseous Xe, CO2, and SF6 mixtures at different densities. The shielding corrections of the nuclei in helium and xenon atoms were taken as calculated with relativistic effects. With the present‐day value of σ( 3 He) and σ(Xe), we have obtained magnetic moment of μ( 129 Xe) = +0.6918451(70)μN for 'bare' nuclei.